1998
DOI: 10.1083/jcb.143.2.333
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamin-related GTPase, Dnm1p, Controls Mitochondrial Morphology in Yeast

Abstract: The Saccharomyces cerevisiae Dnm1 protein is structurally related to dynamin, a GTPase required for membrane scission during endocytosis. Here we show that Dnm1p is essential for the maintenance of mitochondrial morphology. Disruption of the DNM1 gene causes the wild-type network of tubular mitochondrial membranes to collapse to one side of the cell but does not affect the morphology or distribution of other cytoplasmic organelles. Dnm1 proteins containing point mutations in the predicted GTP-binding domain or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

29
358
2
10

Year Published

2000
2000
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 381 publications
(399 citation statements)
references
References 72 publications
(117 reference statements)
29
358
2
10
Order By: Relevance
“…The role of the Dnm1p GTPase in mitochondrial dynamics was first uncovered in a screen for yeast mutants with defective mitochondrial morphology [8]. Subsequent studies (described above) suggested that loss of Dnm1p function blocked mitochondrial fission but allowed the fusion of mitochondrial tips to continue, resulting in the formation of elaborate net-like structures [9,10].…”
Section: Fission and The Outer Membrane Gtpase Dnm1pmentioning
confidence: 99%
See 3 more Smart Citations
“…The role of the Dnm1p GTPase in mitochondrial dynamics was first uncovered in a screen for yeast mutants with defective mitochondrial morphology [8]. Subsequent studies (described above) suggested that loss of Dnm1p function blocked mitochondrial fission but allowed the fusion of mitochondrial tips to continue, resulting in the formation of elaborate net-like structures [9,10].…”
Section: Fission and The Outer Membrane Gtpase Dnm1pmentioning
confidence: 99%
“…Biochemical analyses detect a cytoplasmic pool of Dnm1p in yeast cells [8] and of Drp1 in mammalian cells [26]. In vivo, however, a large proportion of these proteins assembles into punctate structures on the outer mitochondrial membrane [8,26].…”
Section: Fission and The Outer Membrane Gtpase Dnm1pmentioning
confidence: 99%
See 2 more Smart Citations
“…Mitochondria also appear to be victimized by another protein complex, one that mediates mitochondrial fission. Fission and fusion of mitochondria occur every few minutes in healthy cells, both yeast and mammalian (Otsuga et al, 1998;Legros et al, 2002). Organelle fission may be required to send mitochondria to distant sites where ATP is required, whereas fusion appears to be required for genetic complementation and maintenance of healthy mitochondria.…”
Section: The Victim Mitochondrionmentioning
confidence: 99%